Second Life in-world travel guide - Percival, Sean (Que Pub., 2008)
Some new users to Second Life may find that it can be very difficult to navigate this new 3D space and even harder to find some of the more interesting places to visit. Many of the best places to visit in Second Life have remained a secret to the most active and seasoned users, until now! Now there is a guide for everyone who wants to access the top destinations on Second Life. "This book provides over 200 destinations in six areas - shopping, entertainment, education, real life in Second Life, adults only, and where to live" to " over 100 top destinations in shopping, entertainment, adults only, virtual travel, education, and where to live. Answering questions like - where to go for a night out on the town, how to find the best shopping experience or find a specific area like Adidas. The book briefly covers the basics of navigating Second Life with tips on flying, teleporting and creating landmarks, then jumps into the main areas of travel. It also includes profiles of some of the people behind these locations. In most cases they are just as colorful as some of the places they create. Each location will be highlighted with a brief write up, screen shots, and location information